2018
DOI: 10.3389/fphys.2018.00337
|View full text |Cite
|
Sign up to set email alerts
|

Ticagrelor Improves Endothelial Function by Decreasing Circulating Epidermal Growth Factor (EGF)

Abstract: Ticagrelor is one of the most powerful P2Y12 inhibitor. We have recently reported that, in patients with concomitant Stable Coronary Artery Disease (SCAD) and Chronic Obstructive Pulmonary Disease (COPD) undergoing percutaneous coronary intervention (PCI), treatment with ticagrelor, as compared to clopidogrel, is associated with an improvement of the endothelial function (Clinical Trial NCT02519608). In the present study, we showed that, in the same population, after 1 month treatment with ticagrelor, but not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
1
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 33 publications
1
25
1
2
Order By: Relevance
“…In acute coronary syndrome (ACS) patients, treatment with ticagrelor resulted in a reduced number of cardiovascular events and in improved peripheral arterial function compared to clopidogrel [3][4][5], suggesting that ticagrelor, beside its antiplatelet activity, modulates biological processes involved in cardiovascular protection. In patients with stable CAD and concomitant chronic obstructive pulmonary disease (COPD), we have shown that ticagrelor, compared with clopidogrel, is superior in improving biological markers of endothelial function [2,6]. These benefits are consistent with observations in patients with stable CAD and concomitant diabetes in which treatment with ticagrelor led to higher improvement of endothelial dysfunction in comparison to ticagrelor [7].…”
Section: Introductionsupporting
confidence: 83%
See 3 more Smart Citations
“…In acute coronary syndrome (ACS) patients, treatment with ticagrelor resulted in a reduced number of cardiovascular events and in improved peripheral arterial function compared to clopidogrel [3][4][5], suggesting that ticagrelor, beside its antiplatelet activity, modulates biological processes involved in cardiovascular protection. In patients with stable CAD and concomitant chronic obstructive pulmonary disease (COPD), we have shown that ticagrelor, compared with clopidogrel, is superior in improving biological markers of endothelial function [2,6]. These benefits are consistent with observations in patients with stable CAD and concomitant diabetes in which treatment with ticagrelor led to higher improvement of endothelial dysfunction in comparison to ticagrelor [7].…”
Section: Introductionsupporting
confidence: 83%
“…High levels of EGF and its receptor EGFR have been detected in lung tissue specimens of COPD patients [86] and high airway immunoreactivity has been associated to mucin hypersecretion in COPD [87]. EGF is involved in endothelial dysfunction, neointimal hyperplasia, cardiac hypertrophy and remodeling [88] and, as shown by us, reduction in circulating levels of EGF could be involved in the ticagrelor-mediated improvement of endothelial function in stable CAD/COPD patients [2]. The cross-talk between EGF and Notch signaling is well characterized: EGF and Notch pathways can cooperate in either synergistic or antagonistic fashion in malignancies [89] and the EGF, via EGFR, acts as a negative regulator of HES1 expression in keratinocytes [90].…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…Bioavailability of endothelial NO synthase (eNOS) generated NO is decreased in SCD by extracellular hemoglobin which scavenges NO [32,33]. Ticagrelor had positive effects on eNOS activity in endothelial cells [34][35][36]. Adenosine A 2A receptor agonists decreased hypoxia/ reoxygenation-induced tissue inflammation in a mouse model and in patients with SCD [37,38].…”
Section: Introductionmentioning
confidence: 99%